According to European Landscape Convention Historical and Archaeological New Approach - Demir, Sara; Demirel, Öner (Hayrullah KAHYA, 2018)
According to European Landscape Convention, all landscapes should be planned, designed, protected, restored and managed depending on their natural and cultural landscape values. However, the archeological relicts on landscapes and their temporal depth are not taken into account during this assessment process of natural and cultural features of landscapes. In this context, the historical landscape character classification method was developed to analyze the landscape relicts caused by mankind. This study aims to investigate the temporal depth of landscape and emphasize the importance of archeological past on the landscape architecture discipline. Because of this fact, the historical landscape character was determined, the specific data sources were listed and the process of the historical landscape character classification was investigated, the historical landscape and their temporal depth were described and finally the suitable land use decisions were analyzed first time with this new approach under the landscape architecture discipline in the context of European Landscape Convention. It is evaluated the protected areas, monuments and historical relicts with their environment. This study, described the environmental data with their archeological past, can provide to take healthy land use decisions in the historical integrity.

Avrupa Peyzaj sözleşmesi gereği peyzajlar tüm bu kaynak değerleri dikkate alınarak planlanmalı, tasarlanmalı, korunmalı onarılmalı, izlenmeli ve yönetilmelidir. Fakat peyzajların doğal ve kültürel özellikleri değerlendirilirken sahip oldukları arkeolojik kalıntıları ve bunların tarihsel derinliği dikkate alınmamaktadır. Bu bağlamda insanoğlunun peyzaj üzerinde bıraktığı izleri analiz eden tarihi peyzaj karakter sınıflandırması metodu geliştirilmiştir. Bu çalışma peyzaj mimarlığı disiplini kapsamında peyzajların sahip oldukları tarihsel derinliği irdelemeyi ve arkeolojik geçmişin peyzaj mimarlığı disiplini içerisindeki önemini vurgulamayı amaçlamaktadır. Avrupa Peyzaj Sözleşmesi kapsamında Türkiye’ de ilk defa ele alınan ve peyzaj mimarlığına yeni bir yaklaşım sunan bu çalışma ile tarihi peyzaj karakteri tanımlanmış, veri kaynakları belirlenmiş ve tarihi peyzaj karakter sınıflandırma süreçleri araştırılmış, tarihi peyzaj düzeyleri ve bunların tarihsel derinliği irdelenmiş ve son olarak peyzaj mimarlığındaki kullanım alanları araştırılmıştır. Anıt, sit alanları ve diğer tarihi kalıntıları çevreleri ile değerlendiren ve arkeolojik geçmiş içerisinde tanımlayabilen bu çalışmanın çıktıları tarihsel bütünlük içerisinde sağlıklı alan kullanım karalarının alınmasına olanak sunabilir.
AVRUPA PEYZAJ SÖZLEŞMESI GEREĞİ TARİHİ VE ARKEOLOJİK YENİ BİR YAKLAŞIM